Length Scale and Dimensionality of Defects in Epitaxial SnTe Topological Crystalline Insulator Films. Issue 2 (9th January 2017) - Dagdeviren, Omur E.; Zhou, Chao; Zou, Ke; Simon, Georg H.; Albright, Stephen D.; Mandal, Subhasish; Morales‐Acosta, Mayra D.; Zhu, Xiaodong; Ismail‐Beigi, Sohrab; Walker, Frederick J.; Ahn, Charles H.; Schwarz, Udo D.; et al.
Abstract : Topological crystalline insulators (TCIs) are new materials with metallic surface states protected by crystal symmetry. The properties of molecular beam epitaxy grown SnTe TCI on SrTiO3 (001) are investigated using scanning tunneling microscopy (STM), noncontact atomic force microscopy, low‐energy and reflection high‐energy electron diffraction, X‐ray diffraction, Auger electron spectroscopy, and density functional theory. Initially, SnTe (111) and (001) surfaces are observed; however, the (001) surface dominates with increasing film thickness. The films grow island‐by‐island with the [011] direction of SnTe (001) islands rotated up to 7.5° from SrTiO3 [010]. Microscopy reveals that this growth mechanism induces defects on different length scales and dimensions that affect the electronic properties, including point defects (0D); step edges (1D); grain boundaries between islands rotated up to several degrees; edge‐dislocation arrays (2D out‐of‐plane) that serve as periodic nucleation sites for pit growth (2D in‐plane); and screw dislocations (3D). These features cause variations in the surface electronic structure that appear in STM images as standing wave patterns and a nonuniform background superimposed on atomic features. The results indicate that both the growth process and the scanning probe tip can be used to induce symmetry breaking defects that may disrupt the topological states in a controlled way. Abstract : The topological surface states of topological crystalline insulators (TCIs) are protected by crystal symmetry, suggesting that symmetry breaking surface defects may be used to tailor the surface states. It is shown that the epitaxial growth of a TCI creates defects on the mesoscopic and atomic scales that modulate the electronic properties of the surface over these length scales.